Use of the voxel-based morphometry method in the diagnosis of dementia of the Alzheimer type - E. . Andreev; N. . Ananieva; N. . Zalutskaya; I. A. Beltceva; N. . Neznanov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
In recent years, new data in neuroanatomy of patients with various neurodegenerative diseases, including Alzheimer’s disease, were obtained usingmagnetic resonance morphometry. Morphometry of the brain structures using MRI became widespread because of the introduction into clinical practice of a high-resolution mode and the emergence of the voxel transformations of three-dimensional data. The analysis of the brain structures is made more precise with the help of such programs. They help to avoid the «subjectivity» of the operator when the so-called «manual» method of the separation of brain structures. In the current study voxel-based morphometry method revealed a number of morphological characteristicsin the group of patients with dementia of Alzheimer’s type, namely, the gray matter atrophy of the cerebral cortex, subcortical gray matter structures, structures of the white matter of the brain, and the increase in the volume of the ventricular system of the brain. These results are connected with the functional features in this disease.